MENUMBUHKAN GENERASI CAKAP LITERASI DAN BERMENTAL SEHAT DI RUMAH BELAJAR KOJARTIS MELALUI BUKU CERITA BERGAMBAR DAN POHON HARAPAN PADA PROJEK KEPEMIMPINAN MAHASISWA PPG PRAJABATAN - Novalia Novalia; Millenia Safitri; Rina Rina; Sapna Sapira; Ulva Nurma’rifah; Keni Apriliano; Murjainah Murjainah (JURNAL ILMIAH NUSANTARA, 2024)
Literacy is a person's ability to read, write and understand information well. The aim of creating a picture story book with the theme "Anti Bullying" is to help Kojartis children in reading, understanding that building a mentally healthy environment is very important in life. Apart from picture story books, the wishing tree is also one of the activities carried out at the Kojartis learning house. This activity aims to help Kojartis children have better dreams and hopes for life and feel supported in achieving their life goals. These two activities will be held on August 25 2024 in Kojartis. The tools and materials used in making picture story books are: 1) writing a story script; 2) make edits to the story manuscript; 3) create a book image design, using the Canva application; 4) editing the book layout; 5) make revisions; 6) send to ISBN publisher. Meanwhile, the tools and materials for making a wishing tree are: 1) cardboard; 2) scissors; 3) cutter; 4) pencil; 5) eraser; 6) wrong; 7) books for designing; 8) colored mangosteen paper, green and brown; and 9) LED lights. This second activity can help Kojartis children to build literacy skills and build self-confidence to be enthusiastic about achieving their goals and hopes.